Discovery of Novel Sphingosine-1-Phosphate-1 Receptor Agonists for the Treatment of Multiple Sclerosis - Park, Sun Jun; Yeon, Seul Ki; Yoowon Kim; Kim, Hyeon Jeong; KIm Si Won; KIM, JU SHIN; Choi, Ji Won; Byung, Eun Kim; Elijah, Hwejin Lee; Kim Ri-um; SEO, SEON HEE; Lee, Jae Ick; et al. (American Chemical Society, 2022)
The sphingosine-1-phosphate-1 (S1P1) receptor agonists have great potential for the treatment of multiple sclerosis (MS) because they can inhibit lymphocyte egress through receptor internalization. We designed and synthesized triazole and isoxazoline derivatives to discover a novel S1P1agonist for MS treatment. Of the two scaffolds, the isoxazoline derivative was determined to have excellent in vitro efficacy and drug-like properties. Among them, compound 21l was found to have superior drug-like properties as well as excellent in vitro efficacies (EC50= 7.03 nM in β-arrestin recruitment and EC50= 11.8 nM in internalization). We also confirmed that 21l effectively inhibited lymphocyte egress in the peripheral lymphocyte count test and significantly improved the clinical score in the experimental autoimmune encephalitis MS mouse model. ？ 2022 American Chemical Society. All rights reserved.